The Effectiveness of Learning Media in Overcoming Learning Difficulties: Student Perceptions - Ridho Ryanto; Agustina Tri Wijayanti; Anik Widiastuti; Agus Riadi (Jurnal Pemberdayaan Masyarakat, 2025)
Technology-based learning media have been proven to enhance learning by making it more engaging and increasing student interaction, motivation, and overall learning outcomes. However, few studies discuss students' perceptions of the types of learning media that effectively overcome their learning difficulties. Therefore, this study aims to determine students' perceptions of effective learning media that can help them overcome their learning difficulties. The quantitative descriptive method used in this study was applied to grade X students at SMAN 1 Ketapang, with samples selected using a proportional random sampling technique. Data were collected through Google Forms questionnaires containing both closed and open-ended questions and analyzed using descriptive statistics and thematic analysis. This study's findings suggest that students' learning difficulties are often attributed to a lack of motivation, focus, and drowsiness. The teacher's delivery method also contributes to these difficulties, as it is less engaging, difficult to follow, and does not provide clear examples. This research highlights the importance of interactive learning media tailored to students' motivational and cognitive needs, as well as the need for regulatory and policy support in implementing these learning media. Through a comprehensive discussion, this research contributes to the development of more effective digital learning.